Persepsi Pemustaka Terhadap Layanan Perpustakaan di Perpustakaan Proklamator Bung Hatta Bukittingi - Effendi, Norilda; Nelisa, Malta (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2012)
The purpose of this research are (1) describe the users perception of the services which provided at Bung Hatta Proclamator’s Library, (2) describe the factors that influence visitor’s perception, in order to create a good perception of the librarian’s service at Bung Hatta Proclamator’s Library. The data were taken by using a Likert scale and conducted by using questionnaire and interviewing, so that the conclusions are correct. The sources of research data was taken from visitors who visit the library by spoken and written method. It was collected by informants as the original speakers. The result of the research is the perception about a good library service, so that the users are happy to come to the library. Keywords: perception; library services